Theorizing the role of executive heads in international organizations. (December 2018) - Hall, Nina; Woods, Ngaire
International Relations scholars have long neglected the question of leadership in international organizations. The structural turn in International Relations led to an aversion to analysing or theorizing the impact of individuals. Yet, empirical studies suggest that different leaders affect the extent to which international organizations facilitate cooperation among states and/or the capacity of a global agency to deliver public goods. It is difficult to study how and under what conditions leaders have an impact due to the challenges of attributing outcomes to a particular leader and great variation in their powers and operating context. We offer a starting point for overcoming these challenges. We identify three different types of constraints that executive heads face: legal-political, resource and bureaucratic. We argue that leaders can navigate and push back on each of these constraints and provide illustrations of this, drawing on existing literature and interviews with executive heads and senior management of international organizations. Executive heads of international organizations may operate in a constrained environment but this should not stop scholars from studying their impact.